Priapism in the Newborn: Shall We Intervene? - Rachida Laamiri; Nahla Kechiche; Mezri Maatouk; Besma Haggui; Walid Mnari; Mongi Mekki; Abdellatif Nouri (EL-Med-Pub, 2016)
Idiopathic neonatal priapism is rarely published. We report the case of a newborn presenting with priapism on the first day of life and reviewed the published data on the management and the follow up of this condition.